(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Foreign Direct Investment (FDI) is viewed as the backbone of economic development particularly for the developing and immature countries. With the beginning of globalization, many developing countries, for the most part those in Asia, are seeing a tremendous stream of FDIs amid the previous two decades. Foreign Direct investment assumes a vital job in the development of the country. At times domestically accessible capital is deficient with the end goal of by and large development of the nation. India can draw in a lot bigger foreign investments than it has done in the past Foreign Direct Investment (FDI) is viewed as imperative injections motivator to the developing countries to enhance and quicken economic development. Gross domestic product has been characterized as "a total proportion of production equivalent to the whole of the gross values included of all resident, institutional units occupied with production." Since the greater part of the developing countries are encountering an absence of financial resources, dimension of technology and skills. The primary aim of this paper is to define and analyze the relationship and effects of FDI on gross domestic production of country through which we came to a conclusion that FDI have a positive impact on GDP as economic growth, the size of such impact may vary across countries depending on the level of human capital, domestic investment, infrastructure, macroeconomic stability, and trade policies